1928
DOI: 10.1084/jem.48.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Blood Cell Metabolism

Abstract: Although a considerable number of studies liave been published on various phases of the metabolism of blood cells, the relative importance of fermentation and of respiration in their normal activities is still very imperfectly understood. Still more obscure is the metabolic behavior of pathological blood cells, although it m a y be of considerable significance. It is of particular interest, for example, to examinethe activities of the cells of leucemic blood in the light of the recent advances made in our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1930
1930
1963
1963

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…MB provides a case in point, although its metabolic effects are numerous and complex. It is known to stimulate the hexose monophosphate shunt and to increase glucose utilization and CO2 formation; in the presence of MB, erythrocyte oxygen uptake may increase as much as twentyfold (52)(53)(54). Even in the absence of glucose, increased uptake of oxygen is observed that presumably results from utilization of intracellular phosphate esters (51); the rate of breakdown of triose phosphate is increased, and lactate is oxidized to pyruvate (53,55).…”
Section: Discussionmentioning
confidence: 99%
“…MB provides a case in point, although its metabolic effects are numerous and complex. It is known to stimulate the hexose monophosphate shunt and to increase glucose utilization and CO2 formation; in the presence of MB, erythrocyte oxygen uptake may increase as much as twentyfold (52)(53)(54). Even in the absence of glucose, increased uptake of oxygen is observed that presumably results from utilization of intracellular phosphate esters (51); the rate of breakdown of triose phosphate is increased, and lactate is oxidized to pyruvate (53,55).…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be interpreted fairly simply. It has been well known for many years that Mb stimulates oxygen uptake by the red cell (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose-6-phosphate (G-6-P), triphosphopyridine nucleotide (TPN), 3,5,3'-triiodo-L-thyronine (TRITh), L-thyroxine, 3,5-diiodo-L-thyronine (DITh), 3,5-diiodo-L-tyrosine (DIT), and 3,5-dinitro-L-tyrosine (DNT) were obtained from Sigma Chemical Co. The disodium salt of ethylenediaminetetraacetic acid (Disodium Versene®) was obtained from Versenes, Inc.…”
Section: Methodsmentioning
confidence: 99%
“…A few drops of 1 N NaOH were used and the solution was heated to 550 C. to aid solution of TRITh when used in the highest concentration, 3.75 X 10' M. The buffered saline used in these experiments was prepared by the method outlined by Umbreit, Burris and Stauffer (5). The buffer was prepared by dissolving 1.78 Gm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation